Vitamin space greenhouse as an element of advanced biological and technical support for space crews - Yu. A. Berkovich; A. M. Belyak; A. A. Buryak; Yu. I. Smirnov; A. A. Ivanova (Вестник Самарского университета: Аэрокосмическая техника, технологии и машиностроение, 2025)
The design of a vitamin space greenhouse for the Vitacycle-T space experiment on the Russian segment of the ISS is described. The preproduction model of Vitacycle-T successfully passed autonomous tests at the IMBP RAS in 2024. The total area of crops illuminated by LEDs in the vegetation module is 0.4 m2, and its volume is 0.09 m3. The power consumption of the installation is about 870 watts. The average daily yield of cabbage leaves in the space greenhouse was 84 g, and the labor costs for the maintenance of the space experiment during ground tests did not exceed 5.5 minutes per day. The space greenhouse will be able to meet the needs of one astronaut in vitamins A and C. The test results allow us to consider the Vitacycle-T vitamin greenhouse as a promising element for future biological and technical life support systems for space crews.